Tail bifurcation in Gehyra mutilata (Wiegmann, 1834) and an updated compilation of tail abnormality records in Gekkota - Evan S.H. Quah; Lee L. Grismer (Department of Biology Victor Valley College, 2024)
We present the first detailed record of tail bifurcation in Gehyra mutilata from Sabah, Malaysian Borneo. In addition, we compile and update the records of tail abnormalities in the Gekkota based on the latest taxonomy. In total, 69 species from 36 genera and six families within the Gekkota were recorded to have tail malformations. The family Gekkonidae was represented by the highest number of species (46 species), followed by the Diplodactylidae (8), Phyllodactylidae (7), Sphaerodactylidae (4), Eublepharidae (2), and Pygopodidae (2).